2015
DOI: 10.1016/j.immuni.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase MYSM1 Regulates Innate Immunity through Inactivation of TRAF3 and TRAF6 Complexes

Abstract: Pattern-recognition receptors (PRRs) including Toll-like receptors, RIG-I-like receptors, and cytoplasmic DNA receptors are essential for protection against pathogens but require tight control to avert inflammatory diseases. The mechanisms underlying this strict regulation are unclear. MYSM1 was previously described as a key component of epigenetic signaling machinery. We found that in response to microbial stimuli, MYSM1 accumulated in the cytoplasm where it interacted with and inactivated TRAF3 and TRAF6 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 38 publications
3
97
0
Order By: Relevance
“…)22, and innate immunity(Panda et al . )23. In the current study, there were far higher levels of TRAF6, IL-1β, IL-6, IL-8, and IL-33 in the debris group, demonstrating TRAF6 plays a key role in the process of aseptic inflammatory loosening.…”
Section: Discussionsupporting
confidence: 44%
“…)22, and innate immunity(Panda et al . )23. In the current study, there were far higher levels of TRAF6, IL-1β, IL-6, IL-8, and IL-33 in the debris group, demonstrating TRAF6 plays a key role in the process of aseptic inflammatory loosening.…”
Section: Discussionsupporting
confidence: 44%
“…40 The present study revealed that Mysm1 is required for expression of IRF2 and IRF8 in preserving self-renewal of HSC 23, 24, 25 and in governing lineage commitment of HSC. 26, 27 IRF2 functions as a suppressor of IFN-I signaling by occupying the IRF consensus site on target genes and subsequently preventing DNA binding by IRF1, 41 which has an important role in maintaining quiescent HSC pool.…”
Section: Discussionmentioning
confidence: 53%
“…In response to PRR triggering, TRAF6 and TRAF3 undergo K63-linked polyubiquitinaton, enabling these molecules to act as scaffolds for the recruitment and subsequent proximity-dependent activation of "downstream" signalling molecules (Hacker et al, 2006;Panda et al, 2015). TRAF6 and TRAF3 are critical points of convergence for many PRR pathways that control the transcriptional induction of innate immune mediators.…”
Section: Lvs Blocks Proximal Polyubiquitination and Phosphorylationmentioning
confidence: 99%
“…Immunoprecipitation and immunoblot analyses were performed as detailed in our recent study (Panda et al, 2015). Immunoprecipitation and immunoblot analyses were performed as detailed in our recent study (Panda et al, 2015).…”
Section: Infection Of Bone Marrow-derived Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation